Survey of standard protocols for endodontic treatment in Chitwan, Nepal - Kayastha, Pujan Kranti; Shakya, Merina; Shrestha, Lipika (Journal of Chitwan Medical College, 2021)
Background: Endodontics is one of the fastest-growing disciplines which involves the introduction of many new instruments, materials, and techniques. This study aimed to assess the practice of the international standard protocol during the endodontic treatment among dentists in Chitwan, Nepal. Methods: The present cross-sectional study was conducted on August 2020 among the dentist working in Chitwan, Nepal. 120 questionnaires were distributed to the dentist working in Chitwan, Nepal. The data were collected and descriptive analysis was done using SPSS ver. 22. Results: From the total respondent, 104 were included in the survey. Fully filled form and those who perform endodontic treatment were included in the survey for further analysis. Cotton rolls with suction (93.3) and a radiograph with a file in the canal (85.6%) was the most common method for isolation and working length determination respectively. Most of the respondents (81.7% ) used k-files with 84.6% following step-back technique for instrumentation of root canal. Autoclave is mostly (47.1%) used sterilization procedure autoclave. Sodium Hypochlorite and calcium hydroxide (CH) are the most common chemicals used for irrigation and intracanal medication respectively. Eugenol based sealer (76%) was the most common intracanal sealer used for obturation used commonly (82.7%) for cold lateral condensation technique. Cavit (89.4%) was the most popular temporary filling material. Difficulty cases are mostly referred (86.3%) for endodontic consultation. Conclusions: Upgrading and reinforcement of knowledge about newer materials and techniques following protocols is required for endodontic treatment.